Nutrient absorption curves in papaya (Carica papaya L.) cv. “Pococí” during vegetative growth, flowering and the beginning of the harvest period - Fallas, Róger (2014)
In a commercial papaya farm located at Guácimo, Costa Rica, the requirements of nutrients, and the nutrient absorption curves for the Costa Rican high-yielding papaya hybrid “Pococí”, were established. The experiment was carried out in 2010 collecting complete plants, approximately monthly through the phenological cycle of the crop, from transplant until 9 months after wards. It was estimated that the “Pococí” hybrid (1600 plants per hectare) required approximately 354 kg.ha -1 N, 101 kg.ha -1 P 2 O 5 , 498 kg.ha -1 K 2 O, 174 kg.ha -1 CaO, 106 kg.ha -1 MgO and 40 kg.ha -1 S; these required quantities are mostly higher than those that are normally being applied by present fertilization programs in Costa Rica.